1986
DOI: 10.1172/jci112713
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B metabolism in subjects with deficiency of apolipoproteins CIII and AI. Evidence that apolipoprotein CIII inhibits catabolism of triglyceride-rich lipoproteins by lipoprotein lipase in vivo.

Abstract: Previous data suggest that apolipoprotein (apo) CIII may inhibit both triglyceride hydrolysis by lipoprotein lipase (LPL) and apo E-mediated uptake of triglyceride-rich lipoproteins by the liver. We studied apo B metabolism in very low density (VLDL), intermediate density (IDL), and low density lipoproteins (LDL) in two sisters with apo CiII-apo AI deficiency. The subjects had reduced levels of VLDL triglyceride, normal LDL cholesterol, and near absence of high density lipoprotein (HDL) cholesterol. Compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
233
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(250 citation statements)
references
References 39 publications
15
233
1
Order By: Relevance
“…The genetically determined deficiency of apo-CIII has been shown to increase the rate of TG clearance from plasma by 6-to 7-fold (31). Over-expression of apo-CIII produces hypertriglyceridemia in transgenic mouse models via inhibition of clearance of TG-rich particles (32).…”
Section: Discussionmentioning
confidence: 99%
“…The genetically determined deficiency of apo-CIII has been shown to increase the rate of TG clearance from plasma by 6-to 7-fold (31). Over-expression of apo-CIII produces hypertriglyceridemia in transgenic mouse models via inhibition of clearance of TG-rich particles (32).…”
Section: Discussionmentioning
confidence: 99%
“…Apo C-3, a protein produced by the liver, inhibits lipoprotein lipase. Elevated levels of apo C-3 are associated with higher levels of triglyceride through reduced clearance of triglyceride-rich lipoproteins [46,47]. Apo C-3 was slightly higher, but not significantly, in the insulin resistant subjects.…”
Section: Discussionmentioning
confidence: 89%
“…Second, it is well known that apoC-III is an inhibitor of LPL activity. 19 Third, several studies have shown that apoC-III inhibits receptor-mediated uptake of TRL by the liver. 21,22 Kinetic studies using tracer methodology have confirmed that VLDL-apoC-III is overproduced in overweight insulin-resistant subjects, 15 in hypertriglyceridemic subjects compared with controls, 53 and in centrally, obese men compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…13 Plasma apoC-III concentration is strongly correlated with plasma triglyceride (TG) concentration 14,15 and is increased in insulin-resistant states (overweight or obesity 15 and type II diabetes 16,17 ). Elevated apoC-III has been postulated to contribute to the atherogenic dyslipidemia by the impairment of TRL and HDL metabolism including increased VLDL production and secretion, 18 disturbance of TRL clearance by inhibiting LPL 19 or hepatic lipase, 20 and interfering with TRL and their remnant binding to hepatic lipoprotein receptors. 21,22 Beyond the effects of apoC-III on TRL and HDL metabolism, this apolipoprotein has also been shown to promote inflammation and endothelial cell dysfunction, potentially contributing to atherosclerosis and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%